Green Roof Performance in Water Runoff Reduction - Amaram, Amelia Hathirah; Ahmad, Noor Aliza (Recent Trends in Civil Engineering and Built Environment, 2024)
The process of urbanization may result in a dramatic shift in land use from permeable to the impermeable surface [1]. The new construction of buildings in emerging areas has been connected to urban flood events. The increasing stormwater runoff is a significant concern associated with urbanization. Malaysia's climate is regarded to be dry and hot all year. It is prone to floods and flash floods, particularly during cyclical monsoon cold surge events. Green roofs have the potential to reduce flooding risk by reducing water runoff [2]. The aim of this study is to observe the performance of green roofs in reducing water runoff quantity and to study the effectiveness of green roofs in delaying water runoff. The result showed that green roofs manage to produce a lower average volume of water runoff a the range of 0.440 L to 0.464 L of water runoff from 1.0 L of stormwater in both events. Green roof manages to delay an average of up to 15.3 minutes to release water runoff. Green roof also capable to retain stormwater runoff where it can retain in range of 53.6% to 56% of water runoff. Overall, green roof may become an alternative in reducing water runoff and for a better result, a detailed experiment should be conduct.